2002
DOI: 10.2320/matertrans.43.2643
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties from Room Temperature to 673 K of Mg-0.9 mass%Ca Alloy Containing Lamella Mg<SUB>2</SUB>Ca

Abstract: Tensile properties were investigated from room temperature to 673 K of a binary Mg-0.9 mass%Ca alloy where Mg 2 Ca phase was dispersed as lamella. The 0.2% proof stress significantly increased by the Mg 2 Ca phase in the temperature range investigated. It was suggested that strengthening by stable lamella Mg 2 Ca in the grains and limitation of deformation related to grain boundaries by Mg 2 Ca phase at grain boundaries contribute to improvement of high temperature strength for the Mg-Ca alloy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 15 publications
(21 reference statements)
0
16
0
1
Order By: Relevance
“…In Sample S1 networks of the low-strength intermetallic CuMg 2 [18] and high-strength high-temperature Mg 2 Ca [19] phases (as indexed by XRD) were observed along grain boundaries. Addition of Sn in increasing amounts was observed to mediate formation of finer (and seemingly more continuous) intermetallic CuMg 2 and Mg 2 Ca phases, as revealed by a comparison of Samples S2 and S3 with S1.…”
Section: Resultsmentioning
confidence: 99%
“…In Sample S1 networks of the low-strength intermetallic CuMg 2 [18] and high-strength high-temperature Mg 2 Ca [19] phases (as indexed by XRD) were observed along grain boundaries. Addition of Sn in increasing amounts was observed to mediate formation of finer (and seemingly more continuous) intermetallic CuMg 2 and Mg 2 Ca phases, as revealed by a comparison of Samples S2 and S3 with S1.…”
Section: Resultsmentioning
confidence: 99%
“…Высокочистый маг-ний хотя и обладает относительно высокой коррозион-ной стойкостью и прекрасной биосовместимостью, но не может похвастаться ни хорошей прочностью, ни достаточной пластичностью [8] (деформируемостью), что делает невозможным его практическое применение. Поэтому легирование магния является просто необхо-димым шагом для повышения его механических и био-коррозионных свойств.…”
Section: Introductionunclassified
“…Recently, it has been reported that Mg alloys containing Ca show high creep resistance and elevated temperature strength. [8][9][10][11][12] Indeed, Ca is an effective fire retardant. 13) For commercial applications, Ca is a desirable additional element to Mg because of its lower cost than that of RE.…”
Section: Introductionmentioning
confidence: 99%